1949
DOI: 10.1029/tr030i002p00245
|View full text |Cite
|
Sign up to set email alerts
|

Organic productivity of an Atoll

Abstract: The production of organic matter by phytoplankton in the waters in and around the northern Marshall Islands is extremely low. The amount of plankton swept across the reefs of these islands by the wind‐driven currents is grossly inadequate to support the animals living on the reefs. The reef community, consisting of attached algae and animals, is self‐supporting; all the algae produce at least as much organic matter as all the animals consume. The rate of production of organic matter by an atoll as a whole ‐ wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

1957
1957
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 1 publication
1
68
0
Order By: Relevance
“…The release rates that were estimated in the present study, by assuming gross nutrient uptake was mass-transfer limited (J 2 MTL ), were on the same order as those documented in coral cavities and micro atolls, but were an order of magnitude higher than observed over carbonate sediments (generally a net sink; Wild et al 2005;Eyre et al 2008). The J 2 MTL estimates were also on the same order as modeled MTL gross uptake, J + MTL , for both NO x and PO 4 (Tables 4 and 5, respectively), confirming that rates of nutrient release may indeed be significant over many reefs (Sargent and Austin 1949;Odum and Odum 1955;Atkinson et al 2001) and that recycling is likely to be highly variable in space and time (Steven and Atkinson 2003).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The release rates that were estimated in the present study, by assuming gross nutrient uptake was mass-transfer limited (J 2 MTL ), were on the same order as those documented in coral cavities and micro atolls, but were an order of magnitude higher than observed over carbonate sediments (generally a net sink; Wild et al 2005;Eyre et al 2008). The J 2 MTL estimates were also on the same order as modeled MTL gross uptake, J + MTL , for both NO x and PO 4 (Tables 4 and 5, respectively), confirming that rates of nutrient release may indeed be significant over many reefs (Sargent and Austin 1949;Odum and Odum 1955;Atkinson et al 2001) and that recycling is likely to be highly variable in space and time (Steven and Atkinson 2003).…”
Section: Discussionsupporting
confidence: 61%
“…Despite recycling of limiting nutrients often being cited as explaining the productivity of coral reefs under nutrientlimited conditions (Sargent and Austin 1949;Johannes et al 1972), rates of nutrient release on reefs have rarely been estimated due to the difficulty in quantifying either gross uptake or gross release in the field. A number of studies have simplified nutrient release estimates by Table 3) and release rates (J 2 MTL ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first studies of planktonic food webs in coral reefs have shown that these are characterized by high abundance of zooplankton, which are a food source for corals (Russel 1934, Motoda 1938, high biomasses and metabolic rates of bacteria (Sargent & Austin 1949, Odum & Odum 1955, Sorokin 1973, and large stocks of detritus, which are mainly consumed by zooplankton (Marshal1 1965, Gerber & Marshall 1974. The biomasses and production rates of phytoplankton are generally low, but highly variable (Sournia & Ricard 1976, Lewis 1977, Sournia 1977, Kinsey 1985.…”
Section: Introductionmentioning
confidence: 99%
“…Typical coral reefs are generally considered to be dominated by benthic communities, with a very minor contribution by phytoplankton to primary production (Sargent & Austin 1949, 1954, Odum & Odum 1955, Sournia 1977, Kinsey 1985, Gattuso et al 1993). This generalization does not apply, however, to atoll lagoons where, because of a relatively deep water column and scarcity of coral structures, the pelagic community plays a significant role.…”
Section: Introductionmentioning
confidence: 99%